When I grow up - Zephaniah, Benjamin (Frances Lincoln Children's, 2011)
Maggie is a space scientist! Then there's Michelle the vet, Ness the pilot and Bubblz the mathematical clown... Add a famous book illustrator, a lollipop man, a forest keeper, an architect, a village shopkeeper, an international fashion designer, a zoologist, a farmer and a well-known human rights lawyer- and you have a fantastic range of jobs for the 21st century.